2010
DOI: 10.1007/s12031-010-9443-9
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic PrP Induces Apoptosis of Cell by Disrupting Microtubule Assembly

Abstract: Prion protein (PrP) is able to bind with tubulin and to interfere with the formation of microtubule. To investigate the influence of accumulation of cytosolic PrP in cytoplasm on microtubule, plasmid pcDNA3.1-PrP23-230 expressing human PrP23-230 was introduced into HeLa cells. Immunoprecipitation assays identified the molecular interaction between cytosolic PrP and cellular tubulin. Confocal microscopy showed the co-localization of the expressed cytosolic PrP with tubulin in cytoplasm. Immunofluorescent assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…These mutations generally decrease the ability of tau to bind microtubules, increasing its propensity to form abnormal cytotoxic fibers and compromising the ability of the cell to properly regulate microtubule dynamics. Additional evidence supports the idea that destabilization of the microtubule network may be a primary factor in neurotoxicity induced by PrP Sc [78][79][80][81]. Moreover, an induction of tau hyperphosphorylation by misfolded PrP and a direct interaction between PrP and tau have been demonstrated [82].…”
Section: Interaction Of Prp With Tubulinsupporting
confidence: 69%
“…These mutations generally decrease the ability of tau to bind microtubules, increasing its propensity to form abnormal cytotoxic fibers and compromising the ability of the cell to properly regulate microtubule dynamics. Additional evidence supports the idea that destabilization of the microtubule network may be a primary factor in neurotoxicity induced by PrP Sc [78][79][80][81]. Moreover, an induction of tau hyperphosphorylation by misfolded PrP and a direct interaction between PrP and tau have been demonstrated [82].…”
Section: Interaction Of Prp With Tubulinsupporting
confidence: 69%
“…In this regard, our findings prompted us to hypothesize two levels of regulation of cell apoptosis by PrP C : on microtubules, where an early interaction of PrP C with tubulin can alter microtubule framework integrity (Li et al , 2011), and, later, on the mitochondrial membrane, where it interacts with raft-like microdomains. Finally, since PrP C raft-mediated trafficking appears to strictly depend upon apoptotic triggering, we can also suggest a reappraisal of the previously hypothesized formation of PrP Sc within acidic compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Many previously studies have repeatedly identified that the levels of tubulin decreased in CNS tissues of naturally occurred or experimental human and animal TSEs [15], [16], [17]. Our previous studies have demonstrated that the CJD-associated PrPs can disrupt the cellular microtubule structure through different pathways [18].…”
Section: Introductionmentioning
confidence: 92%